Exploring Psychopathic Traits in David Leslie Johnson’s Film Orphan - Pardi Pardi; Nadhira Muthia (Universitas Islam Sumatera Utara, 2026)
This study examines psychopathic traits through the behavior of the protagonist, Esther, in David Leslie Johnson's movie Orphan (2009), using Hare's (1999) psychopathy framework. A qualitative descriptive approach was employed, with data collected through detailed observation of Esther's actions and interactions in the film. The findings indicate that Esther exhibits core psychopathic traits, including a lack of empathy, poor behavioral control, and manipulativeness. She demonstrates emotional detachment and indifference to the suffering of others, responds impulsively to provocation, and deceives those around her to gain trust and influence. These behaviors reveal a profound disregard for moral and social norms, highlighting that psychopathy can be hidden behind an outwardly innocent appearance. This study contributes to the growing intersection between literary criticism, film studies, and psychological analysis by demonstrating how cinematic narratives can reflect clinically recognized personality disorders. The study underscores the importance of critical evaluation and vigilance in assessing individuals, as external appearances may not reflect underlying psychological dispositions.